2021
DOI: 10.4314/ahs.v21i.3s
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life and associated factors among HIV patients on antiretroviral therapy in North West region of Cameroon

Abstract: Background: There is evidence that Quality of Life (QoL) of People Living with HIV/AIDS (PLHIV) has a significant role in ART retention, treatment adherence, and survival. As a result, QoL is becoming increasingly important for policy- makers, program implementers, and researchers. However, factors associated with QoL, in a culturally diverse country like Cameroon are unknown. Objective: We aimed to assess the QoL of PLHIV on ART and assess the extent to which physical, psychosocial, environ- mental, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Spiritual well-being can contribute positively to the mental and emotional resilience of PLHIV, playing a role in coping with the challenges associated with the disease. Study conducted in the north-west region of Cameroon, reported the highest mean score in the spiritual belief domain, followed by levels of independence, physical, psychological, social, and environmental domains [35].…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual well-being can contribute positively to the mental and emotional resilience of PLHIV, playing a role in coping with the challenges associated with the disease. Study conducted in the north-west region of Cameroon, reported the highest mean score in the spiritual belief domain, followed by levels of independence, physical, psychological, social, and environmental domains [35].…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Though the survival is prolonged, still PLHIV continue to suffer from many physical problems including side effects of therapy like pain and fatigue, etc., mental health issues like depression and social issues like isolation. 5,6,7 All these things determine their health status and impact the quality of life (QOL) of PLHIV. 8 As per the World Health Organization (WHO), 'Quality of Life is an individual's perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns'.…”
Section: Introductionmentioning
confidence: 99%